Propagande catholique, convictions protestantes et duplicité textuelle: "La paix de Dieu" (1685/1690) du comte Gédéon de Reffuge, nouveau converti - Millet, Olivier (Revue d'histoire et de philosophie religieuses, 2005)
The reformed Gédéon de Reffuge, who was imprisoned in the Bastille in 1685, converted there to Roman Catholicism and wrote an appeal to the European Protestants to follow his example. The manuscript of this text, which we found, is very different from the printed publication of 1690, which was censored by Roman Catholic theologians. The manuscript version gives insight into the spiritual crisis that the author went through because of his imprisonment. The count de Reffuge refers to a prophetic illumination in order to legitimate an interpretation of the Bible that justifies his conversion to the King's religion. Paradoxically, in the very act of his abjuration he thus testifies to a Protestant religious culture.